Aspergillus japonicus Biofilms on Lab Fermenter: Development, Temperature, pH Survival Studies, and Drug Resistance - Muddukrishnaiah, K. (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Biofilms are described as a microbial population anchored to a surface and entrenched in a self-produced matrix of polysaccharides. The biofilms forming capacity of Aspergillus japonicus on glass fermenter and its susceptibility over temperature, pH, and drug resistance was evaluated in this study. Materials and Methods: A. japonicus was screened from an annual herb at Pattambi, Kerala. It was identified using fungal universal primers ITS4 and ITS5 at the ITS region of rDNA (NCBI Accession numbers MG833001, MG833000). A. japonicus was cultivated by submerged culture using Potato Dextrose Broth and potato dextrose agar. The formation of biofilms was observed on laboratory fermenter and confirmed by the crystal violet method, followed by a scanning electron microscope (SEM) analysis. The effects of temperature and pH on A. japonicus biofilms formation were studied. The antimicrobial resistance of A. japonicus against fluconazole and clotrimazole was evaluated. Results: The growth curve was obtained from plant infected isolate of the A. japonicus biofilms formation. Biofilms were confirmed by in vitro crystal violet method. SEM analysis showed the massive growth of A. japonicus biofilms. The inocula of 1 × 106 conidia/mL were incubated at 8°C, 20°C, 37°C, 50°C, and 70°C for 180 days. This proves that A. japonicus survives in all temperature conditions. The inocula of 1 × 106 conidia/mL were then incubated at different pH (3, 4, 5, 6, 7, 8, 9, and 10) for 12 days. This shows that biofilms are rapidly formed at pH 5, 6, and 7. A. japonicus exhibits resistant against fluconazole and clotrimazole. Conclusions: The study concludes that biofilms are the most stable, survive for a long time at different temperatures and pH, and also show resistance against fluconazole and clotrimazole. This is the first report of A. japonicus biofilms formation in India.